Pension Finance : Putting the Risks and Costs of Defined Benefit Plans Back Under Your Control - Waring, M. Barton (Hoboken John Wiley, 2012)
For PENSION FINANCE/ "Pension Finance is a comprehensive, integrated, and self-contained offering on the structure, management, and oversight of defined benefit pension plans, carefully composed by a prime observer and practitioner in the defined benefit pension world. . . an important and most needed contribution to defined benefit pension knowledge. Whether a prime academic researcher, experienced public policymaker, seasoned private-sector practitioner, or novice student of retirement finance, the reader is in for a treat: bon appetit!"'Robert C. Merton, MIT "This book is a major advance in the literature of pension finance, breaking much new ground in the market value approach to pension finance. Thorough and hard-hitting, Waring warns that many will consider his blunt views to be 'controversial' or even 'heretical.' But his approach sheds a much-needed bright light on the fundamental nature of pension liability. There are also many valuable suggestions about how to structure an asset portfolio that addresses these now more clearly defined liabilities, given a specific fund's risk tolerance, contingent reserves, back-up resources, and payment schedule."'Martin Leibowitz, Managing Director, Morgan Stanley "The value of Pension Finance is not in propounding any new or novel finance ideas, but in systematically explaining the guts of the actuarial process, and then restating the process in sound terms. After reading this book, those involved in the pension arena will understand the causes of the pension crisis and appreciate how easy the 'right answers' are once those causes are understood."'Frank Fabozzi, Professor of Finance, EDHEC Business School and Editor, The Journal of Portfolio Management "Pension Finance is now the seminal work on the subject and should be required reading for policymakers, practitioners, and plan fiduciaries. Waring makes a compelling and persuasive case that the only way to ensure the long-term viability of defined benefit plans is to accurately measure the true costs and risks of providing the benefits and provisioning accordingly."'Bradley D. Belt, former Director, Pension Benefit Guaranty Corporation, and Senior Managing Director, Milken Institute "Pension Finance draws cross-disciplinary lessons learned the hard way to set in motion a much-needed overhaul of the U.S. defined benefit pension system. Waring's risk management approach will help guide corporate and public plan sponsors to better measure, pay for, and manage their pension assets and liabilities using modern financial principles. Chock-full of examples and sometimes sad lessons from the pension trenches, this book will set the terms of debate for corporate boards and public plan trustees, consultants and actuaries, unions and financial advisors, and most of all, policymakers seeking to return the U.S. retirement system to health." 'Olivia S. Mitchell, Professor of Insurance & Risk Management/Business & Public Policy The Wharton School, University of Pennsylvani
Include Reference and Index
Keywords: Pension trusts--Management -- Pensions--Finance -- Pensions management (Title)